Prevalence of Hepatitis C Virus among blood donors in Blood Bank of Jhalawar Hospital & Medical College Society, Jhalawar Rajasthan - Dr. Manish Kumar; Dr. Yogendra Madan (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Hepatitis C infection continue to be a threat to safe transfusion practices. This study aims to determine the prevalence of Hepatitis- C virus (HCV) among voluntary and replacement blood donors in Blood Bank of Jhalawar Hospital & Medical College Society, Jhalawar, Rajasthan.Material and Methods: A retrospective review of donors record covering the period between Jan 2017 to Dec 2017 at Jhalawar Hospital & Medical College Society, Jhalawar, Rajasthan. The blood collections were taken from the voluntary donors at total 69 blood donation camp and as well as from replacement donors and voluntary donors at blood bank. The blood samples were then obtained by standard procedures of venepuncture. Total 16495 blood donors screened over the period of one year. Antibodies to Hepatitis C virus in serum/plasma is detected by rapid test kit.Results: 34 out of 16495 donor population were positive for Hepatitis C (Prevalence 0.2%).Conclusion: Replacement donors were higher prevalence than the voluntary donors. So, the present study concludes that motivating voluntary blood donors by conducting voluntary blood donation camp is the most effective way of ensuring adequate supplies of safe blood and blood components for transfusion.